A new cotylean polyclad flatworm species from Ghar El Melh lagoon (Northern Tunisia) - Gammoudi, Mehrez (2023)
A new Phrikoceros polyclad species is described from Ghar El Melh lagoon, a natural seawater lagoon situated in the north of Tunisia. Specimens of the new species were handly collected among Tunicates.They were photographed, measured, and fixed with Bouin’s fluid. The embedded specimens in paraplast were serially sectioned at 7 micra, and stained with Azan. DNA was extracted from a small piece of tissue and PCR for partial small and large nuclear ribosomal subunits (18S and 28S) was performed. Our new species is characterized by black spots on the dorsal surface contrary to the white spotted dorsal colour pattern of its congeners. The small, narrow, ovally-elongated pharynx is located in the anterior third of the body and stretches about 1/6 of the entire body length. The mouth opens in the centre of the pharyngeal cavity. The main intestine reaches 7/8 of the body length and extends from the level of the brain, up to almost the distal margin. The male copulatory apparatus is directed to the front and provided with a free prostatic vesicle half being as big as the seminal vesicle and slightly elongated. The penis papilla isarmed with a sclerotized stylet. The female genital pore is located 0.5 mm behind the male one. The vagina is provided with a glandular pouch. We provide some insights into the biology of this species, like the plastic tentacle configuration and the variability of body form and outline. We also include some observations about the protusion of the male copulatory organ. The new species was found among tunicates of the species Ciona intestinalis, suggesting a posible trophic relationship.